Mycobiomes of the Ocular Surface in Bacterial Keratitis Patients - Jayasudha, Rajagopalaboopathi; Chakravarthy, Sama Kalyana; Prashanthi, Gumpili Sai; Sharma, Savitri; Garg, Prashant; Murthy, Somasheila I.; Shivaji, Sisinthy (Frontiers in Ophthalmology, 2022)
Inflammation of the cornea is known as keratitis and bacteria, fungi, protozoans, and viruses are the etiological agents of this disease. Delayed treatment of keratitis could result in loss of vision and under certain severity conditions the removal of an eye and its associated structures. In the current study, the ocular surface (conjunctiva and cornea) mycobiomes of individuals with bacterial keratitis (BK) were compared with the ocular mycobiome (conjunctiva) of healthy individuals (HC), free of any ocular morbidity. Mycobiomes were generated through NGS approach using conjunctival swabs (SW) and corneal scrapings (CR) as the source of DNA from which ITS2 was amplified and sequenced, as a proxy to identify fungi. The results indicated significant changes in the Alpha-diversity indices and in the abundance at the phylum and genera level. Hierarchical clustering using a heatmap showed that the mycobiomes between HC-SW, BK-SW and BK-CR were different. Further, NMDS plots also differentiated the mycobiomes in the three cohorts implying changes dysbiosis in the mycobiomes of the conjunctivae and corneal scrapings of bacterial keratitis individuals compared to control individuals indicative of dysbiosis in keratitis ocular mycobiomes. A preponderance of negative interactions in the hub genera in BK-SW compared to HC-SW further reemphasised the differences in the mycobiomes. The dysbiotic changes at the genera level in BK-SW and BK-CR are discussed with respect to their possible role in causing or exacerbating ocular surface inflammation. These results demonstrate dysbiosis in the ocular mycobiome in bacterial keratitis patients compared to healthy controls for the first time.